Liberal or restrictive dilemma—that’s a CLASSIC! - Watson, Ximena; Cecconi, Maurizio (Annals of Translational Medicine, 2017)
Hjortrup et al. recently published the results of the CLASSIC study (1). In this randomised parallel group multicentre feasibility study, the effects of a protocol restricting resuscitation fluid vs. a standard care protocol were assessed after initial resuscitation in patients with septic shock. Patients in nine ICU’s who fulfilled the criteria for sepsis, circulatory impairment and ongoing shock as defined by the requirement for continuous infusion of noradrenaline, and who had received at least 30 mL/kg of crystalloid fluid were randomised to the restrictive or standard protocol. In both intervention groups, the administration of resuscitation fluid was per protocol and a mean arterial pressure (MAP) of at least 65 mmHg was targeted and maintained with noradrenaline infusion. In the fluid restrictive group, patients received fluid boluses of isotonic crystalloid only if there was evidence of severe hypoperfusion defined as either: plasma concentration of lactate of at least 4 mmol/ L, MAP below 50 mmHg in spite of noradrenaline infusion, mottling beyond the edge of the kneecap or oliguria.